Multilayered oxide ceramic bodies with tailored sintering behavior.

By adding La2O3 and MgO to the multi-layer oxidized ceramic blanks and adjusting chemical composition, the problems of uneven color distribution and sintering deformation are solved, and the effect of no deformation and uniform color after sintering is achieved, which improves the aesthetics and function of the tooth restoration material.

JP7660437B2Active Publication Date: 2025-04-11IVOCLAR VIVADENT AG
View PDF 38 Cites 0 Cited by

Patent Information

Application Number
JP2021092293
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2016-12-23
Filing Date
2021-06-01
Publication Date
2025-04-11
Estimated Expiration
2037-12-23

AI Technical Summary

Technical Problem

The prior art When preparing multi-layer oxidized ceramic bodies, the color distribution is uneven and deformation is easily caused when sintered at high temperature, which affects the aesthetics and function of the tooth restoration material.

Method used

Multi-layer oxidized ceramic blanks containing La2O3 and MgO are used to adjust the chemical composition and additives of different levels to ensure the sintering behavior of each layer during the sintering process, avoid deformation, and achieve uniform color distribution through chromatography technology.

Benefits of technology

The multi-layer oxidized ceramic body is achieved without deformation during the sintering process and the color distribution is uniform, which improves the aesthetics and functional performance of the tooth restoration material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660437000018
    Figure 0007660437000018
  • Figure 0007660437000019
    Figure 0007660437000019
  • Figure 0007660437000020
    Figure 0007660437000020
Patent Text Reader

Abstract

To provide multilayer oxide ceramic bodies suitable for dental applications.SOLUTION: The invention relates to multilayer oxide ceramic bodies, in particular, presintered multilayer oxide ceramic blanks and oxide ceramic green bodies, which comprise at least two different layers and are suitable for dental applications, where at least one layer contains La2O3 and the at least two different layers differ in their content of La2O3. These bodies can be thermally densified by further sintering without distortion and are therefore particularly suitable for production of dental restorations. The invention also relates to a process for production of such multilayer oxide ceramic bodies, and to a process for production of dental restorations using the multilayer oxide ceramic bodies.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to multilayer oxide ceramic bodies suitable for dental applications, in particular pre-sintered multilayer oxide ceramic blanks and oxide ceramic green bodies. These bodies can be thermally densified by further sintering without distortion and are therefore particularly suitable for the production of dental restorations with excellent mechanical properties and very high fitting accuracy, making it possible to very closely mimic the optical properties of natural teeth. The present invention also relates to a process for producing such a multilayer oxide ceramic body, as well as a process for producing dental restorations using the multilayer oxide ceramic body. [Background technology]

[0002] For many years, oxide ceramic materials have been used to produce dental implants and restorations. Such ceramics are typically based on zirconia in the form of tetragonal zirconia polycrystal (TZP). Pure ZrO2 undergoes a tetragonal to monoclinic phase transition accompanied by a significant increase in volume at temperatures below 950 °C. To maintain zirconia in its tetragonal form at room temperature, the use of additives such as Y2O3, CeO2, MgO, or CaO is necessary. These additives block the tetragonal to monoclinic transition, thereby resulting in a metastable state in which zirconia is completely or partially in its tetragonal form. When a crack forms in such a metastable tetragonal zirconia ceramic, the stress at the crack tip induces a local transition from the tetragonal to the monoclinic form, and the accompanying increase in volume effectively opposes crack propagation. This so-called transformation toughening mechanism results in high toughness of stabilized zirconia ceramics (Hannink et al., J. Am. Ceram. Soc. 2000, vol. 83, pp. 461-487). This, combined with the bioinert properties of zirconia, has led to the use of doped TZP in orthopedics and for dental restorations. Today, in particular, tetragonal zirconia polycrystals stabilized with Y2O3 (Y-TZP), usually with the addition of Al2O3 (about 0.25 wt%), are widely used as all-ceramic dental biomaterials (Denry et al., Dental Materials 2008, vol. 24, pp. 299-307).

[0003] Various processes for preparing ceramics are known, with the preferred processes being (i) axial or cold isostatic pressing (CIP) followed by conventional sintering, (ii) slip casting followed by conventional sintering, and (iii) hot pressing (HP) or hot isostatic pressing (HIP).

[0004] In dental applications, the preparation of ceramic materials often involves two densification steps separated by a molding step. Thus, the ceramic material can be pressed or cast and then pre-sintered to an intermediate open pore state. Molding or pre-forming of the ceramic material can then be performed, followed by final thermal densification by further sintering.

[0005] In order to improve the aesthetic appearance of dental restorations, ceramics used as dental restorative materials often need to be stained. Various possibilities are known for staining ceramic materials.

[0006] One approach to obtain colored dental ceramic materials uses coloring of ceramic materials in a porous state by infiltration with a solution of metal compounds. Typically, the porous structure is dried, fully or partially infiltrated with a coloring solution, the surface is cleaned, the infiltrated structure is dried, the porous structure is optionally infiltrated with additional coloring solution, and finally sintered.

[0007] US 6,709,694 B1 describes a process for the coloring of oxide ceramics in a porous or absorbent state with solutions of salts or complexes of transition metals.

[0008] EP1486476A1 describes a method for producing a metal salt, a solvent, and a M n A process is described for coloring presintered ceramic bodies using a solution containing polyethylene glycol having a molecular weight in the range of 1,000 to 200,000.

[0009] This approach suffers from a complicated process for the dental technician and a low homogeneity of the obtained color distribution. Moreover, depending on the concentration of the coloring ions, the enlargement factor may vary within the colored layer, which leads to stress between the colored and non-colored areas during the final sintering step.

[0010] Another approach involves pre-coloring the zirconia powder by co-precipitation of the zirconia with a coloring compound or by contacting the zirconia powder with a solution of a coloring compound to obtain pre-colored primary and secondary particles with different powder characteristics.

[0011] No. 5,011,403A describes the production of colored brackets by compressing and sintering the powder obtained by adding a colored transition metal oxide to a partially stabilized zirconia powder, where the transition metal oxide is incorporated in powder form or by spraying a solution of a water-soluble salt of the transition metal oxide onto the zirconia powder.

[0012] No. 5,263,858 A describes the production of ivory-colored sintered zirconia bodies that can be used as brackets in orthodontic applications, in which a mixed powder is prepared by (A) co-precipitation and calcination of a solution containing a zirconium compound, a stabilizer, erbium, and praseodymium, or (B) mixing a solution of erbium and praseodymium compounds with a zirconia powder containing a stabilizer, and a compact is formed from the resulting powder and sintered.

[0013] No. 5,656,564A describes a colored sintered zirconia body for orthodontic bracket material produced by wet mixing stabilized zirconia powder with a coloring substance, and molding and sintering the resulting powder.

[0014] US 6,713,421 A describes a blank based on a ceramic composition containing zirconia and at least one of the oxides of aluminum, gallium, germanium and indium, and further coloring additives. The ceramic composition is prepared by coprecipitation and calcination.

[0015] A further approach involves the colouring of ready-to-press ceramic powders by coating techniques.

[0016] US 2007 / 292597 A1 describes a process for producing monochromatic and multi-chromatic blanks and dental molded parts, in which an oxide powder is coated with a coloring substance, the colored powder is compressed to form a molded body, and the compressed body is sintered.

[0017] US 2008 / 0274440 A1 describes an abutment for a dental implant, comprising a one-piece support structure for a dental prosthesis, made from a ceramic material and colored to match the color of the dental prosthesis to the surrounding tooth material and gingival tissue. Coloring of the abutment can be achieved, according to US 2007 / 292597 A1, inter alia, by coating an oxide powder with a coloring substance.

[0018] Yet another technique involves coloring by mixing colored and uncolored powders and pigments together.

[0019] US 6,379,593 describes a process for producing multi-colored bodies suitable for further processing to form dental restorations, in which differently colored ceramic materials are introduced successively into an extrusion die, compressed into the shape of a body, and sintered.

[0020] US 2007 / 272120 A1 describes a ceramic block comprising first and second ceramic compounds having different optical properties and further comprising a transition region between the ceramic compounds where the resulting gradient of variation in the optical properties is substantially constant.

[0021] US 2008 / 064011 A1 describes a multi-colored molded body having differently colored main and intermediate layers, where the color change between the intermediate layers occurs in a direction opposite to the direction of the color change between the main layers. Multi-colored molded bodies are also disclosed having differently colored main layers and intermediate layers that contain a mixture of the materials of the main layers.

[0022] WO2008 / 083358A1 describes a multi-coloured dental blank having concentric inner and outer zones of different colouration.

[0023] US2010 / 0216095A1 describes the production of colored dental ceramics in which Y-TZP is mixed with a coloring component to obtain a substantially homogeneous agglomerate material, and the differently colored agglomerates are mixed, pressed and sintered.

[0024] US2011 / 0189636A1 describes a molded body containing differently colored first and second components, where the second component is disposed within the first component such that a curved interface is formed.

[0025] US 2012 / 139141 A1 describes the production of a colored zirconia product by treating a Y-TZP powder with a solution of a colorant to obtain a pigment powder, mixing the pigment powder with an uncolored powder, compressing the mixed powder and sintering it.

[0026] It has been shown that state-of-the-art processes suffer from different and incompatible sintering kinetics of the various ceramic powders used therein (e.g., combinations of pigmented and non-pigmented powders, or combinations of differently pigmented powders, etc.). When different powders are combined to form different layers of a multi-layer ceramic body, the difference in these sintering kinetics leads to distortion of the multi-layer ceramic body upon sintering. Such distortion is undesirable, especially for dental applications.

[0027] WO2015 / 011079A1 describes a multilayer oxide ceramic blank for producing dental restorations and a process for producing the same, in which the sintering behavior of the different layers is matched. However, in order to mimic the properties of natural teeth, It has been shown that the colour, and especially the translucency properties, of these oxide ceramics are not optimal in all cases. [Prior art documents] [Patent documents]

[0028] [Patent Document 1] U.S. Patent No. 6,709,694 [Patent Document 2] European Patent Application Publication No. 1486476 [Patent Document 3] U.S. Pat. No. 5,011,403 [Patent Document 4] U.S. Pat. No. 5,263,858 [Patent Document 5] U.S. Pat. No. 5,656,564 [Patent Document 6] U.S. Patent No. 6,713,421 [Patent Document 7] US Patent Application Publication No. 2007 / 292597 [Patent Document 8] US Patent No. 2008 / 0274440 [Patent Document 9] U.S. Patent No. 6,379,593 [Patent Document 10] US Patent Application Publication No. 2007 / 272120 [Patent Document 11] US Patent Application Publication No. 2008 / 064011 [Patent Document 12] International Publication No. 2008 / 083358 [Patent Document 13] US Patent Application Publication No. 2010 / 0216095 [Patent Document 14] US Patent Application Publication No. 2011 / 0189636 [Patent Document 15] US Patent Application Publication No. 2012 / 139141 [Non-patent literature]

[0029] [Non-Patent Document 1] Hannink et al., J. Am. Ceram. Soc. 2000, 83, 461-487 [Non-Patent Document 2] Denry et al., Dental Materials 2008, Vol. 24, pp. 299-307 Summary of the Invention [Means for solving the problem]

[0030] The object of the present invention is therefore to provide a multilayer oxide ceramic body, in particular an oxide ceramic blank with differently colored layers, which does not show distortion during thermal densification, and in particular to provide a ceramic body suitable for the production of dental products, having high fitting precision, reliability and ease of processing by the dental technician, as well as a very good aesthetic appearance of the final densified ceramic.

[0031] This object is achieved by a pre-sintered multilayer oxide ceramic blank according to claims 1 to 17 and 20. The subject of the invention is also a process for producing a multilayer oxide ceramic green body according to claims 18 to 20, a blank or green body according to claims 21 to 24 and a multilayer oxide ceramic blank or green body obtainable by this process according to claim 25, as well as a process for producing a dental restoration according to claims 26 to 29.

[0032] The pre-sintered multilayer oxide ceramic blank according to the present invention is characterized in that it comprises at least two different layers, at least one of which contains La2O3, said at least two different layers differing in their La2O3 content.

[0033] Surprisingly, it has been shown that the blanks according to the invention show no or essentially no distortion during pre-sintering or final sintering. In particular, these blanks do not suffer from significant differences in the sintering kinetics or shrinkage behavior between the different layers. Surprisingly, it has been found that the addition of La2O3 is particularly suitable for adjusting the sintering behavior of the different layers. In particular, the addition of La2O3 makes it possible to compensate for the different sintering behavior caused by different properties of the starting powders, such as the BET specific surface area, grain size, grain shape, pressing behavior and chemical composition of the powder, in particular by additives for improving color and translucency properties.

[0034] According to the invention, blanks in which at least one layer contains 0.005 to 5 wt. %, in particular 0.01 to 1.0 wt. %, preferably 0.025 to 0.5 wt. %, most preferably 0.03 to 0.20 wt. % La2O3 are preferred.

[0035] Furthermore, blanks in which at least one layer comprises Al2O3 and / or MgO are preferred. It has been shown that the sintering behavior of the different layers can be particularly well matched by the additional use of Al2O3 and MgO.

[0036] Preferred are blanks in which at least one layer contains 0.001 to 5 wt%, in particular 0.005 to 1.0 wt%, preferably 0.01 to 0.20 wt%, most preferably 0.02 to 0.10 wt% Al2O3 and / or MgO.

[0037] In particular, blanks are preferred in which at least one layer contains 0.001 to 5 wt%, in particular 0.005 to 1.0 wt%, preferably 0.01 to 0.10 wt%, most preferably 0.02 to 0.05 wt% Al2O3, and likewise blanks are preferred in which at least one layer contains 0.001 to 5 wt%, in particular 0.005 to 1.0 wt%, preferably 0.01 to 0.10 wt%, most preferably 0.01 to 0.03 wt% MgO.

[0038] Furthermore, blanks in which at least one layer comprises Al2O3 and MgO in a weight ratio of 10:1 to 1:10, preferably 5:1 to 1:1, particularly preferably 4:1 to 2:1, are preferred.

[0039] Particularly preferred are such blanks in which at least one layer comprises La2O3, especially in the amounts defined above, and at least one other layer comprises Al2O3 and / or MgO, especially in the amounts defined above.

[0040] In a preferred embodiment, at least one layer, preferably all layers, of the blank according to the invention contain Y2O3. At least one layer, preferably all layers, preferably contain 0.1 to 20.0 wt%, in particular 1.0 to 15.0 wt%, preferably 5.0 to 12.5 wt%, most preferably 7.0 to 9.5 wt% Y2O3. The addition of Y2O3 has been shown to be particularly suitable for imparting to the blank and the dental product produced therefrom a color, in particular a translucent property, which can particularly well mimic the corresponding properties of natural tooth material. Furthermore, it is preferred that at least two different layers differ in their Y2O3 content. It is particularly preferred that the difference in Y2O3 content between the layer with the lowest Y2O3 content and the layer with the highest Y2O3 content is at least 1.0 wt%, preferably at least 1.5 wt%, in particular at least 1.8 wt%, more preferably at least 2.0 wt%, in particular at least 2.5 wt%, even more preferably at least 3.0 wt%, in particular at least 3.5 wt% and most preferably at least 3.8 wt%.

[0041] According to the invention, it is particularly preferred that the layer with the lowest Y2O3 content comprises La2O3 and / or the layer with the highest Y2O3 content comprises Al2O3 and / or MgO. It has unexpectedly been shown that the use of La2O3 in the layers with low Y2O3 content on the one hand and Al2O3 and / or MgO in the layers with high Y2O3 content on the other hand is particularly suitable for adjusting the sintering behavior of layers with different amounts of Y2O3.

[0042] It is particularly preferred that the layer with the lowest Y2O3 content contains 0.005 to 5 wt%, in particular 0.01 to 1.0 wt%, preferably 0.25 to 0.09 wt%, most preferably 0.5 to 0.8 wt% La2O3. The layer with the highest Y2O3 content contains 0.001 to 5 wt%, in particular 0.005 to 1.0 wt%, preferably 0.01 to 0.20 wt%, most preferably 0.02 to 0.10 wt% Al2O3 and / or MgO. It is even more preferred that it contains

[0043] In a particularly preferred embodiment of the blank according to the invention, the proportion by weight of La2O3 in each of the at least two different layers is given by the following formula: m(La2O3)=m min (La2O3)+(m max (Y2O3)-m(Y2O3))×f It is calculated by During the ceremony, m(La2O3) is the fraction by weight of La2O3 in each layer, m min (La2O3) is the minimum percentage by weight of La2O3 in all layers, m(Y2O3) is the weight fraction of Y2O3 in each layer, m max (Y2O3) is the maximum percentage by weight of Y2O3 in any layer, f is in the range of 0.01 to 1.00, in particular in the range of 0.03 to 0.20, preferably in the range of 0.06 to 0.10, particularly preferably in the range of 0.065 to 0.085, most preferably in the range of 0.081 to 0.083.

[0044] Oxide ceramics are generally highly crystalline ceramic materials based on oxide compounds and contain, at most, a very low proportion of glass phase. Typical oxide ceramics are based on ZrO2, Al2O3, TiO2, MgO, combinations, solid solutions and composites thereof. Oxide ceramics based on ZrO2 and / or Al2O3 are particularly preferred.

[0045] Oxide ceramics based on zirconia, in particular tetragonal zirconia polycrystals (TZP) suitably stabilized, for example, by Y2O3, CeO2, MgO and / or CaO, are particularly preferred. Particularly preferred oxide ceramics are yttria-stabilized tetragonal zirconia polycrystals (Y-TZP), cerium oxide-stabilized tetragonal zirconia polycrystals (Ce-TZP), zirconia-toughened alumina (ZTA) and alumina-toughened zirconia (ATZ).

[0046] It is particularly preferred that the total amount of ZrO2, Y2O3, and HfO2 in the zirconia-based oxide ceramic is at least 99.0 wt%. It is further preferred that the zirconia-based oxide ceramic contains the following components in the amounts shown: Y2O3 2.0 to 10.0 wt%, especially 4.5 to 6.0 wt%, HfO2 up to 5.0wt%, Al2O3 up to 5.0wt%, especially up to 0.5wt%, SiO2 up to 0.1 wt% and Na2O max 0.1wt%.

[0047] The blank according to the invention is particularly suitable for producing dental products, in particular for producing multi-unit dental restorations. The blank according to the invention is particularly suitable for producing dental restorations, in particular bridges, which include two or more units.

[0048] Different layers of the blank usually have different colors. Within the meaning of this application, the terms "color" and "colored" refer to the color, brightness and / or color of the layers. or translucency.

[0049] "Translucency" is the light transmitting ability of a material, object, or layer, i.e., the ratio of transmitted light intensity to the incident light intensity.

[0050] The color is L * a * They can also be characterized by b-values ​​or by color codes commonly used in the dental industry. Examples of such color codes are Vitapan classical® and Vita 3D Master®, both from VITA Zahnfabrik H. Rauter GmbH & Co. KG, and Chromascop® from Ivoclar Vivadent AG.

[0051] It is particularly preferred that the colours of the different layers are within the range of natural tooth colours.

[0052] The layers are preferably planar layers arranged parallel to one another. The blank is preferably in the form of a rectangular block, a disk, a cylinder, a dental preform, an abutment preform, a tooth sector, a horseshoe, a cone, a cone segment, a pyramid, a pyramid segment, a torus, a torus segment, a truncated cone, a truncated cone segment, a tube, a tube segment, a sphere, a sphere segment, an ellipse or an ellipse segment, in each case with or without a notch or ledge.

[0053] In a further preferred embodiment, the blank according to the invention has a distortion coefficient of less than 0.4, in particular less than 0.35, in particular less than 0.3, preferably less than 0.25, even more preferably less than 0.2 and most preferably less than 0.1.

number

number

[0054] The Vickers hardness according to standard ISO 14705:2008 is particularly suitable for predicting the sintering behavior of different regions within a pre-sintered multi-layer blank.

[0055] The calculation of the distortion factor should generally be based on multiple measurements of Vickers hardness at locations encompassing each of the different layers of the blank. It may also be possible to include measurements of Vickers hardness at internal surfaces of the blank that are accessible by cutting the blank into individual segments or discs. It is even more preferred that the measurements encompass a portion of the blank that is at least as large as a typical restoration that will be produced from the blank.

[0056] In one embodiment, the distortion coefficient is calculated based on measurements of HV at measurement points distributed at regular intervals along a first line intersecting different layers of the outer surface of the blank, with additional measurement points distributed at regular intervals along a second line parallel to the first line at the center of the blank and at the surface, preferably accessible by cutting the blank.

[0057] The regular interval between the measurement points along the first and second lines shall be 5 mm or less. It is particularly preferred that the central surface of the blank is made accessible by cutting the blank in half.

[0058] The HV values ​​of pre-sintered ceramic materials for CAD / CAM applications are typically in the range of 300 to 1000 MPa.

[0059] The present invention also relates to a multilayer oxide ceramic green body for producing a dental restoration comprising at least two different layers, at least one layer containing La2O3, said at least two different layers differing in their La2O3 content. Preferred embodiments of the oxide ceramic green body are as defined above for the oxide ceramic blank according to the invention.

[0060] In a preferred embodiment, the oxide ceramic green body according to the invention has a distortion coefficient of less than 0.4, in particular less than 0.35, in particular less than 0.3, preferably less than 0.25, even more preferably less than 0.2 and most preferably less than 0.1.

number

number

[0061] In the sintering step, the green body is preferably heated at a heating rate of 1 to 10 K / min, preferably 5 K / min, to a temperature 50 K below the desired sintering temperature, and at 1 to 3 K / min, preferably 1 K / min, to the desired sintering temperature, preferably about 1100° C., and maintained at this temperature for 30 to 480 minutes, preferably 120 to 180 minutes. In a particular embodiment, the green body is heated at a heating rate of 5 K / min to a temperature 50 K below the desired sintering temperature, and at 1 K / min to the desired sintering temperature, preferably about 1100° C., and maintained at this temperature for 120 minutes. If the green body contains a binder, the sintering step is typically preceded by a debinding step, which comprises heating to 300° C., 500° C. or 700° C. at a heating rate of 0.1 to 0.5 K / min, preferably 0.1 to 0.3 K / min, more preferably 0.25 K / min, with a holding time of 20 to 120 minutes, preferably 60 minutes, at 300° C. and / or 500° C. and / or 700° C. In certain embodiments, the debinding step is The steps included heating to 700°C at a heating rate of 0.25 K / min with hold times of 300°C, 500°C, and 60 min at 700°C.

[0062] Within the meaning of this application, the term "green body" generally refers to an unsintered ceramic material, typically produced by densification, such as compaction, of oxide ceramic powders. Pertaining to the body.

[0063] The sintering behavior of the at least two different layers of the blank according to the invention or of the green body according to the invention is preferably adjusted so that the blank or green body can be sintered without distortion.

[0064] Furthermore, the present invention relates to a process for producing the blank according to the invention and the green body according to the invention, said process comprising the steps of: (a) providing at least one first oxide ceramic material and one second oxide ceramic material, the at least one first oxide ceramic material and the one second oxide ceramic material differing with respect to their chemical composition; (b) La2O3 is added to at least one of the oxide ceramic materials; and (c) optionally, Al2O3 and / or MgO are added to at least one of the oxide ceramic materials; It is characterized by:

[0065] It is further preferred that at least one of the oxide ceramic materials, preferably both oxide ceramic materials, contains Y2O3, in which case it is particularly preferred that the first oxide ceramic material and the second oxide ceramic material differ with respect to their Y2O3 content.

[0066] In a preferred embodiment of the process according to the invention, at least one oxide ceramic material is infiltrated with La2O3 and / or at least one oxide ceramic material is infiltrated with Al2O3 and / or MgO. Suitable infiltration methods are described, for example, in US 2014 / 135200 A1.

[0067] In another preferred embodiment of the process according to the invention, at least one oxide ceramic material is coated with La2O3 and / or at least one oxide ceramic material is coated with Al2O3 and / or MgO. Suitable coating methods are described, for example, in US 2007 / 292597 A1.

[0068] According to a further preferred embodiment, the process according to the invention comprises the steps of: (d) forming layers of oxide ceramic material and arranging the layers one on top of the other; (e) the oxide ceramic material is compacted, in particular compressed, with a view to obtaining a green body; and (f) Optionally, the green body is pre-sintered to obtain a pre-sintered ceramic blank. The present invention is further characterized by the following.

[0069] In a particularly preferred embodiment, the layers of oxide ceramic material exhibit a continuous change in composition from the composition of the first oxide ceramic material to the composition of the second oxide ceramic material, which makes it possible to form a continuous color gradient without visible boundaries and transitions between the individual layers.

[0070] Finally, the present invention also relates to a multilayer oxide ceramic blank or green body obtainable by the process according to the invention. Preferred embodiments of the oxide ceramic blank or green body are as described above for the oxide ceramic blank according to the invention.

[0071] The multilayer oxide ceramic body according to the invention is particularly suitable for producing dental restorations. The invention therefore also relates to a process for producing dental restorations, in which a blank according to the invention or a green body according to the invention is used.

[0072] In the process for producing a dental restoration, the multilayer oxide ceramic body is preferably given a desired geometric shape in order to obtain a shaped ceramic product. The shaping is preferably performed by machining. The machining is typically controlled by a computer, preferably using a CAD / CAM process.

[0073] In a preferred embodiment, the molded ceramic product has the shape of a dental framework or abutment, or a monolithic fully anatomical dental restoration, especially a multi-unit dental restoration. It is further preferred that the shaped ceramic article be densely sintered. [Brief description of the drawings]

[0074] [Figure 1]The results, described below, are shown in Figure 1A (overview) and 1B (detailed view). [Diagram 2] The results, described below, are shown in Figure 2A (overview) and 2B (detailed view). [Diagram 3] The results, described below, are shown in Figure 3A (overview) and 3B (detailed view). [Figure 4] The results, described below, are shown in Figure 4A (overview) and 4B (detailed view). [Diagram 5] The results, described below, are shown in Figure 5A (overview) and 5B (detailed view). [Figure 6] The results, described below, are shown in Figures 6A (overview) and 6B (detailed view). [Figure 7] The results, described below, are shown in FIG. 7 (debindered and presintered blank) and FIG. 8 (densely sintered blank in transmitted light). [Figure 8] The results, described below, are shown in FIG. 7 (debindered and presintered blank) and FIG. 8 (densely sintered blank in transmitted light). [Figure 9] The results, described below, are shown in Figures 9A (overview) and 9B (detailed view). [Figure 10] The results, described below, are shown in Figure 10A (overview) and 10B (detailed view). [Figure 11] The results, described below, are shown in Figures 11A (overview) and 11B (detailed view). [Figure 12] The results, described below, are shown in Figures 12A (overview) and 12B (detailed view). [Figure 13] The results, described below, are shown in Figures 13A (overview) and 13B (detailed view). [Figure 14] The results, described below, are shown in Figures 14A (overview) and 14B (detailed view). [Figure 15] The results, described below, are shown in FIG. [Figure 16] The results, described below, are shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0075] The invention will now be described in more detail with reference to examples. EXAMPLES

[0076] General Process for Treating Oxide Powders with Colorants and / or Dopants The processing of the oxide powders in the following examples was carried out similarly to US 2014 / 135200 A1.

[0077] For this purpose, an aqueous treatment solution was prepared containing an appropriate amount of water-soluble nitrates of the elements with which the oxide powder was intended to be treated. An appropriate amount of oxide powder (e.g., 1,000 g) was introduced into the mixing vessel of an "EL1" laboratory mixer (Eirich, Hardheim), which further had an agitator (star agitator) and a spray nozzle (0.3 mm hollow cone) for applying the solution. The mixing vessel was set to move at a speed of 13 m / s, and the oxide powder placed therein was uniformly stirred by the agitator. Then, with the aid of a 120S / DV type peristaltic pump (Watson Marlow, Rommerskirchen; speed 170 rpm), about 0.1 g of treatment solution per 1 g of oxide powder was applied to the oxide powder through the spray nozzle, thereby uniformly infiltrating the oxide powder with the treatment solution.

[0078] Example 1 Tuning the sintering behavior of two-layer blanks made of zirconia powders with different yttrium contents by doping with La2O3 To prepare the colored zirconia powders, commercially available zirconia powders (TOSOH TZ-PX-471 and TOSOH Zpex Smile) were used as raw materials and treated with solutions of nitrates of coloring elements and optionally lanthanum as dopant according to the table below using a common process, thereby obtaining powders suitable for the dentin layer (L1) and for the cutting layer (L2). [Table 1] 1) of the total weight of the oxide mixture after sintering 2) Contains 9.25wt% Y2O3 and 0.048wt% Al2O3 3) Contains 7.37wt% Y2O3 and 0.048wt% Al2O3 4) Calculated as Fe2O3 5) Calculated as Cr2O3 6) Calculated as Pr2O3 7) Calculated as Er2O3 8) Calculated as La2O3

[0079] Then, about 10 g of each of the colored zirconia powders were introduced into the pressing die (diameter about 40 mm) of a laboratory axial press in two layers (L1 at the bottom, L2 at the top) one after the other and axially densified under a pressure of about 160 MPa. The green bodies thus obtained were debindered and presintered using the firing program described below. 60K / min to 120℃, 24K / min to 200℃, 10K / min to 320℃, Bring to 1050°C at 60K / min and hold for 3 hours.

[0080] Sections of approximately 2 mm thickness were cut from the thus obtained debindered and presintered blanks using a saw (IsoMet 4000, Buehler, Esslingen). The edge of a paper or ruler was placed on the two lower outer edges of the section as a reference line and the area of ​​maximum bending was measured under a stereomicroscope (SZX 16, Olympus, Hamburg). The results are shown in Figure 1A (overview) and 1B (detailed view). The presintered blanks showed negligible bending of only 0.03 mm.

[0081] Finally, the presintered blank pieces were densely sintered in a Programat S1 furnace (Ivoclar Vivadent AG, Schaan) using the firing and cooling program described below. 600K / h to 900℃, hold for 0.5h, 200K / h to 1500℃, hold for 2 hours, 600K / hour to 900℃, Heat to 300℃ at 500K / hour.

[0082] Sections of the densely sintered blanks were then measured under the stereomicroscope described above. The results are shown in Figures 2A (overview) and 2B (detailed view). The densely sintered blanks showed no measurable bending.

[0083] Example 2 (comparison) Sintering behavior of two-layer blanks made of zirconia powders with different yttrium contents without doping with La2O3 Example 1 was repeated identically, but without the addition of lanthanum as a dopant. The results for the debindered and pre-sintered blanks are shown in Figures 3A (overview) and 3B (detailed). In these figures it can be clearly seen that the dentin layer (L1) has shrunk more than the cutting layer (L2), whereby the blank has acquired a convex shape. The bending of the blank was 0.36 mm. The results after dense sintering of the blanks are shown in Figures 4A (overview) and 4B (detailed). Even the densely sintered blanks still showed a bending of 0.04 mm afterwards.

[0084] Example 3 Tuning the sintering behavior of four-layer blanks made of zirconia powders with different yttrium contents by doping with La2O3 For the preparation of colored zirconia powders, commercial zirconia powders (TOSOH TZ-PX-471 and TOSOH Zpex Smile) were used as raw materials and treated with a solution of nitrates of coloring elements and optionally lanthanum as dopant according to the table below using a general process. Thereby, a powder suitable for the dentin layer (L1) and a powder suitable for the cutting layer (L4) were obtained. These powders were further obtained as two powders suitable for the intermediate layer by mixing them in a ratio of 1:2 or 2:1, respectively, using a shaker mixer (Turbula, WAB, Muttenz). [Table 2] 1) of the total weight of the oxide mixture after sintering 2) Contains 9.25wt% Y2O3 and 0.048wt% Al2O3 3) Contains 7.37wt% Y2O3 and 0.048wt% Al2O3 4) Calculated as Fe2O3 5) Calculated as Cr2O3 6) Calculated as Pr2O3 7) Calculated as Er2O3 8) Calculated as La2O3

[0085] About 19 g of each of the colored zirconia powders were then introduced into a pressurizing die (diameter about 40 mm) of a laboratory axial compressor in four layers (L1 at the bottom, L4 at the top) one after the other and axially densified under a pressure of about 160 MPa. The green bodies thus obtained were debindered and presintered using the firing program described below. 60K / min to 120℃, 24K / min to 200℃, 10K / min to 320℃, Bring to 1050°C at 60K / min and hold for 3 hours.

[0086] Sections of approximately 2 mm thickness were cut from the thus obtained debindered and pre-sintered blanks using a saw (IsoMet 4000, Buehler, Esslingen). A piece of paper or a ruler was placed on the two lower outer edges of the section as a reference line and the area of ​​maximum bending was measured under a stereomicroscope (SZX 16, Olympus, Hamburg). The results are shown in Figures 5A (overview) and 5B (detailed view). The pre-sintered blanks showed negligible bending of only 0.02 mm.

[0087] Furthermore, the development of the Vickers hardness HV5 on the layers was measured on sections of the pre-sintered blanks using a hardness tester (ZHU 0.2, Zwick Roell, Ulm) at 10 measuring points spaced 1.5 mm apart in each case. The determined hardness values ​​are listed in the table below. [Table 3]

[0088] From these values, a distortion coefficient of d=0.114 was calculated.

[0089] Finally, the blanks were densely sintered in a Programat S1 furnace (Ivoclar Vivadent AG, Schaan) using the following firing and cooling program: 600K / h to 900℃, hold for 0.5h, 200K / h to 1500℃, hold for 2 hours, 600K / hour to 900℃, Heat to 300℃ at 500K / hour.

[0090] From the densely sintered blank thus obtained, sections of approximately 2 mm thickness were then cut as described above and measured under a stereomicroscope. The results are shown in Figures 6A (overview) and 6B (detailed view). The densely sintered blank showed no measurable bending.

[0091] Example 4 Tuning the sintering behavior of four-layer blanks made of zirconia powders with different yttrium contents by doping with La2O3 Example 3 was repeated with larger batches. For this purpose, about 115 g of each of the colored zirconia powders obtained as in Example 3 were introduced into the pressing die (diameter about 100 mm) of a powder press in four layers (at the bottom: L1, at the top: L4) one after the other and axially densified under a pressure of about 160 MPa. The blanks were first debindered as described in Example 3, presintered and then densely sintered. Sections with a thickness of about 2 mm in each case were cut from the blanks thus obtained and measured under a stereomicroscope. The results are shown in FIG. 7 (debindered and presintered blanks) and FIG. 8 (densely sintered blanks in transmitted light). The blanks did not show any measurable bending.

[0092] Furthermore, the development of the Vickers hardness HV5 on the layers was measured on sections of the pre-sintered blanks using a hardness testing machine (ZHU 0.2, Zwick Roell, ulm) at 10 measuring points spaced 2 mm apart in each case. The determined hardness values ​​are listed in the table below. [Table 4]

[0093] From these values, a distortion coefficient of d=0.088 was calculated.

[0094] Example 5 Tuning the sintering behavior of blanks with continuous color and translucency profiles made of zirconia powders with different yttrium contents by doping with La2O3 For the preparation of colored zirconia powders, commercial zirconia powders (TOSOH TZ-PX-471 and TOSOH Zpex Smile) were used as raw materials and treated with a solution of nitrates of coloring elements and optionally lanthanum as dopant according to the table below using a general process, thereby obtaining powders suitable for the dentin layer (L1) and cutting layer (L2). [Table 5] 1) of the total weight of the oxide mixture after sintering 2) Contains 9.25wt% Y2O3 and 0.048wt% Al2O3 3) Contains 7.37wt% Y2O3 and 0.048wt% Al2O3 4) Calculated as Fe2O3 5) Calculated as Mn2O3 6) Calculated as Pr2O3 7) Calculated as Tb2O3 8) Calculated as Er2O3 9) Calculated as La2O3

[0095] The colored zirconia powder was then introduced into a pressing die (diameter about 100 mm) of a powder press in the form of a continuous gradient using a suitable packing process and axially densified under a pressure of about 160 MPa. The green body thus obtained was debindered and presintered using the firing program described below. 60K / min to 120℃, 24K / min to 200℃, 10K / min to 320℃, Bring to 1050°C at 60K / min and hold for 3 hours.

[0096] Sections of approximately 2 mm thickness were cut from the thus obtained debindered and pre-sintered blanks using a saw (IsoMet 4000, Buehler, Esslingen). A piece of paper or a ruler was placed on the two lower outer edges of the section as a reference line and the area of ​​maximum bending was measured under a stereomicroscope (SZX 16, Olympus, Hamburg). The results are shown in Figures 9A (overview) and 9B (detailed view). The pre-sintered blanks showed negligible bending of only 0.01 mm.

[0097] Furthermore, the evolution of the Vickers hardness HV5 on the gradient was measured on sections of the pre-sintered blanks using a hardness testing machine (ZHU 0.2, Zwick Roell, Ulm) at 10 measuring points spaced 1.5 mm apart in each case. The determined hardness values ​​are listed in the table below. [Table 6]

[0098] From these values, a distortion coefficient of d=0.083 was calculated.

[0099] Finally, the presintered blank pieces were densely sintered in a Programat S1 furnace (Ivoclar Vivadent AG, Schaan) using the firing and cooling program described below. 600K / h to 900℃, hold for 0.5h, 200K / h to 1500℃, hold for 2 hours, 600K / hour to 900℃, Heat to 300℃ at 500K / hour.

[0100] Sections of the densely sintered blanks were then examined under a stereomicroscope as described above. The results are shown in Figures 10A (overview) and 10B (detailed view). The densely sintered blanks showed no measurable bending.

[0101] Example 6 Tuning the sintering behavior of two-layer blanks made of zirconia powders with different yttrium contents by doping with La2O3, Al2O3, and MgO For the preparation of colored zirconia powders, commercial zirconia powders (TOSOH Zpex and TOSOH Zpex Smile) were used as raw materials and treated with solutions of nitrates of coloring elements and optionally lanthanum or aluminum and magnesium as dopants using a general process according to the table below, thereby obtaining powders suitable for the dentin layer (L1) and cutting layer (L2). [Table 7] 1) of the total weight of the oxide mixture after sintering 2) Contains 9.25wt% Y2O3 and 0.048wt% Al2O3 3) Contains 5.36wt% Y2O3 and 0.048wt% Al2O3 4) Calculated as Fe2O3 5) Calculated as Mn2O3 6) Calculated as Pr2O3 7) Calculated as Tb2O3 8) Calculated as Er2O3 9) Calculated as Al2O3 10) Calculated as MgO 11) Calculated as La2O3

[0102] Then, about 10 g of each of the colored zirconia powders were introduced into the pressing die (diameter about 40 mm) of a laboratory axial press in two layers (L1 at the bottom, L2 at the top) one after the other and axially densified under a pressure of about 160 MPa. The green bodies thus obtained were debindered and presintered using the firing program described below. 60K / min to 120℃, 24K / min to 200℃, 10K / min to 320℃, Bring to 1010°C at 60K / min and hold for 3 hours.

[0103] Sections of approximately 2 mm thickness were cut from the thus obtained debindered and pre-sintered blanks using a saw (IsoMet 4000, Buehler, Esslingen). A ruler was placed on the two lower outer edges of the section as a reference line and the area of ​​maximum bending was measured under a stereomicroscope (SZX 16, Olympus, Hamburg). The results are shown in Figures 11A (overview) and 11B (detailed view). The pre-sintered blanks showed negligible bending of only 0.03 mm.

[0104] Finally, the presintered blank pieces were densely sintered in a Programat S1 furnace (Ivoclar Vivadent AG, Schaan) using the firing and cooling program described below. 600K / h to 900℃, hold for 0.5h, 200K / h to 1500℃, hold for 2 hours, 600K / hour to 900℃, Heat to 300℃ at 500K / hour.

[0105] Sections of the densely sintered blanks were again measured under a stereomicroscope as described above. The results are shown in Figures 12A (overview) and 12B (detailed view). The densely sintered blanks showed no measurable bending.

[0106] Example 7 (comparison) Sintering behavior of two-layer blanks made of zirconia powders with different yttrium contents without doping with La2O3 Example 6 was repeated identically, but without the addition of dopants (lanthanum, aluminum, magnesium). The results for the debindered and pre-sintered blanks are shown in Figures 13A (overview) and 13B (detailed view). In these figures it can be clearly seen that the dentin layer (L1) has shrunk more than the cutting layer (L2), whereby the blank has acquired a convex shape. The bending of the blank was 0.74 mm. The results after dense sintering of the blanks are shown in Figures 14A (overview) and 14B (detailed view). It can be seen that even the densely sintered blanks still showed a bending of 0.05 mm.

[0107] Example 6 was repeated in the same manner, but without the addition of dopants (lanthanum, aluminum, magnesium). The results for the debindered and presintered blanks are shown in Figures 13A (overview) and 13B (detailed view).

[0108] Example 8 Tuning the sintering behavior of blanks with continuous color and translucency gradients made of zirconia powders with different yttrium contents by doping with La2O3, Al2O3, and MgO For the preparation of colored zirconia powders, commercial zirconia powders (TOSOH Zpex and TOSOH Zpex Smile) were used as raw materials and treated with solutions of nitrates of coloring elements and optionally lanthanum or aluminum and magnesium as dopants using a general process according to the table below, thereby obtaining powders suitable for the dentin layer (L1) and cutting layer (L2). [Table 8] 1) of the total weight of the oxide mixture after sintering 2) Contains 9.25wt% Y2O3 and 0.048wt% Al2O3 3) Contains 5.36wt% Y2O3 and 0.048wt% Al2O3 4)Calculated as Fe2O3 5) Calculated as Mn2O3 6) Calculated as Pr2O3 7) Calculated as Tb2O3 8) Calculated as Er2O3 9) Calculated as Al2O3 10) Calculated as MgO 11) Calculated as La2O3

[0109] The pigmented zirconia powder was then loaded into a pressing die (diameter about 100 mm) of a powder press in the form of a continuous gradient using a suitable packing process and axially densified at a pressure of about 160 MPa. The green body thus obtained was debindered and pre-sintered using the firing program described below. 60K / min to 120℃, 24K / min to 200℃, 10K / min to 320℃, Bring to 1050°C at 60K / min and hold for 3 hours.

[0110] Sections approximately 2 mm thick were cut from the debindered and presintered blanks thus obtained using a saw (IsoMet 4000, Buehler, Esslingen). The results are shown in Figure 15. The presintered blanks showed negligible bending.

[0111] Furthermore, the evolution of the Vickers hardness HV5 on the gradient was measured on sections of the pre-sintered blanks using a hardness testing machine (ZHU 0.2, Zwick Roell, Ulm) at 10 measuring points spaced 2 mm apart in each case. The determined hardness values ​​are listed in the table below. [Table 9]

[0112] From these values, a distortion coefficient of d=0.22 was calculated.

[0113] Finally, the presintered blank pieces were densely sintered in a Programat S1 furnace (Ivoclar Vivadent AG, Schaan) using the firing and cooling program described below. 600K / h to 900℃, hold for 0.5h, 200K / h to 1500℃, hold for 2 hours, 600K / hour to 900℃, Heat to 300℃ at 500K / hour.

[0114] Sections of the densely sintered blank were again measured under the stereomicroscope as described above, and the results are shown in Figure 16. The densely sintered blank showed negligible bending.

[0115] The present invention provides, for example, the following items. (Item 1) A pre-sintered multi-layer oxide ceramic blank for producing a dental restoration, said blank comprising at least two different layers, at least one layer being La 2 O 3 and the at least two different layers are 2 O 3 Pre-sintered multi-layered oxide ceramic blanks differing in content. (Item 2) At least one layer contains 0.005 to 5 wt%, in particular 0.01 to 1.0 wt%, preferably 0.025 to 0.5 wt%, most preferably 0.03 to 0.20 wt% La. 2 O 3 The blank according to item 1, comprising: (Item 3) At least one layer is Al 2 O 3 and / or MgO. (Item 4) At least one layer is La 2 O 3 and at least one other layer is Al 2 O 3 and / or MgO. (Item 5) The at least one layer contains 0.001 to 5 wt. %, in particular 0.005 to 1.0 wt. %, preferably 0.01 to 0.20 wt. %, most preferably 0.02 to 0.10 wt. % Al. 2 O 3 and / or MgO. (Item 6) The at least one layer contains 0.001 to 5 wt. %, in particular 0.005 to 1.0 wt. %, preferably 0.01 to 0.10 wt. %, most preferably 0.02 to 0.05 wt. % Al. 2 O 3 6. The blank according to any one of items 3 to 5, comprising: (Item 7) 7. The blank according to any one of items 3 to 6, wherein the at least one layer comprises 0.001 to 5 wt.%, in particular 0.005 to 1.0 wt.%, preferably 0.01 to 0.10 wt.%, most preferably 0.01 to 0.03 wt.% MgO. (Item 8) The at least one layer is Al 2 O 3 and MgO in a weight ratio of 10:1 to 1:10, preferably 5:1 to 1:1, particularly preferably 4:1 to 2:1. (Item 9) At least one layer, preferably all layers, are 2 O 3 In particular, one or preferably all layers contain 0.1 to 20.0 wt. %, in particular 1.0 to 15.0 wt. %, preferably 5.0 to 12.5 wt. %, most preferably 7.0 to 9.5 wt. % Y 2 O 3 9. The blank according to any one of items 1 to 8, comprising: (Item 10) The at least two different layers have their Y 2 O 3 The Y 2 O 3 Layer with highest Y content 2 O 3 Between the layers with Y content 2 O 3 10. The blank according to item 9, wherein the difference in content is at least 1.0 wt%, preferably at least 1.5 wt%, in particular at least 1.8 wt%, even more preferably at least 2.0 wt%, in particular at least 2.5 wt%, even more preferably at least 3.0 wt%, in particular at least 3.5 wt%, and most preferably at least 3.8 wt%. (Item 11) The lowest Y 2 O 3 The layer has a La content of 0.005 to 5 wt.%, in particular 0.01 to 1.0 wt.%, preferably 0.25 to 0.9 wt.%, most preferably 0.5 to 0.8 wt.%. 2 O 3 The blank according to item 10, comprising: (Item 12) The best Y 2 O 3 The layer has a content of 0.001 to 5 wt%, in particular 0.005 to 1.0 wt%, preferably 0.01 to 0.20 wt%, most preferably 0.02 to 0.1 wt% Al. 2 O 3 and / or MgO. (Item 13) In each of the at least two different layers, La 2 O 3 The weight ratio of m(La 2 O 3 )=m min (La 2 O 3 )+(m max (Y 2 O 3 )-m(Y 2 O 3 ))×f It is calculated by During the ceremony, m(La 2 O 3 ) is the La 2 O 3 is the percentage by weight of m min (La 2 O 3 ) is the La of all layers 2 O 3 is a minimum percentage by weight of m(Y 2 O 3 ) is the Y 2 O 3 is the percentage by weight of m max (Y 2 O 3 ) is the Y 2 O 3 is the maximum percentage by weight of 13. The blank according to any one of items 9 to 12, wherein f is in the range of 0.01 to 1.00, in particular in the range of 0.03 to 0.20, preferably in the range of 0.06 to 0.10, particularly preferably in the range of 0.065 to 0.085 and most preferably in the range of 0.081 to 0.083. (Item 14) 14. The blank according to any one of the preceding claims, wherein the oxide ceramic is based on zirconia, preferably on stabilized tetragonal zirconia polycrystals. (Item 15) 15. The blank according to any one of items 1 to 14, suitable for producing a multi-unit dental restoration, preferably a dental restoration comprising two or more units, in particular a bridge comprising two or more units. (Item 16) 16. The blank of any one of the preceding claims, wherein the at least two different layers have different colors. (Item 17) A distortion coefficient of less than 0.4, in particular less than 0.35, in particular less than 0.3, preferably less than 0.25, even more preferably less than 0.2, most preferably less than 0.1.

number

number

Claims

1. A pre-sintered multi-layer oxide ceramic blank for producing dental restorations, wherein the oxide ceramic is based on zirconia and the blank comprises at least two different layers, at least one layer comprising at least one colouring element selected from Fe, Cr, Er, Pr, Mn and Tb, and at least one layer comprising 0.005 to 5 wt % La. 2 O 3 and at least one layer comprises 0.1 to 20.0 wt % Y 2 O 3 and the at least two different layers include those La 2 O 3 and Y 2 O 3 wherein the lowest Y 2 O 3 The layer having the La content 2 O 3 A pre-sintered multi-layer oxide ceramic blank comprising:

2. At least one layer contains 0.01 to 1.0 wt %, preferably 0.025 to 0.5 wt %, and most preferably 0.03 to 0.20 wt % La. 2 O 3 The blank of claim 1 , comprising:

3. At least one layer is Al 2 O 3 3. A blank according to claim 1 or 2, further comprising:

4. At least one layer is La 2 O 3 and at least one other layer is Al 2 O 3 and / or MgO.

5. The at least one layer contains 0.001 to 5 wt %, in particular 0.005 to 1.0 wt %, preferably 0.01 to 0.20 wt %, and most preferably 0.02 to 0.10 wt % Al. 2 O 3 and / or MgO.

6. The at least one layer contains 0.001 to 5 wt %, in particular 0.005 to 1.0 wt %, preferably 0.01 to 0.10 wt %, most preferably 0.02 to 0.05 wt % Al. 2 O 3 6. The blank of claim 3 , comprising:

7. 7. A blank according to any one of claims 3 to 6, wherein the at least one layer comprises 0.001 to 5 wt.%, in particular 0.005 to 1.0 wt.%, preferably 0.01 to 0.10 wt.%, most preferably 0.01 to 0.03 wt.% MgO.

8. The at least one layer is Al 2 O 3 and MgO in a weight ratio of 10:1 to 1:10, preferably 5:1 to 1:1, particularly preferably 4:1 to 2:

1.

9. At least one layer, and preferably all layers, contain 1.0 to 15.0 wt %, preferably 5.0 to 12.5 wt %, and most preferably 7.0 to 9.5 wt % Y. 2 O 3 9. The blank of claim 1 , comprising:

10. The lowest Y 2 O 3 Layer with highest Y content 2 O 3 Between the layer having the Y content 2 O 3 10. A blank according to claim 9, wherein the difference in content is at least 1.0 wt%, preferably at least 1.5 wt%, in particular at least 1.8 wt%, even more preferably at least 2.0 wt%, in particular at least 2.5 wt%, even more preferably at least 3.0 wt%, in particular at least 3.5 wt%, and most preferably at least 3.8 wt%.

11. The lowest Y 2 O 3 The layer has a La content of 0.005 to 5 wt %, in particular 0.01 to 1.0 wt %, preferably 0.25 to 0.9 wt %, most preferably 0.5 to 0.8 wt %. 2 O 3 The blank of claim 10 comprising:

12. The best Y 2 O 3 The layer having an Al content 2 O 3 and / or MgO, preferably 0.001 to 5 wt %, in particular 0.005 to 1.0 wt %, preferably 0.01 to 0.20 wt %, most preferably 0.02 to 0.1 wt % Al. 2 O 3 and / or MgO.

13. La in each of the at least two different layers 2 O 3 The weight ratio of m (No) 2 Oh 3 )=・・ min (No) 2 Oh 3 )+(m max (Y) 2 Oh 3 )-m(Y 2 Oh 3 ))×f It is calculated by During the ceremony, m (La 2 O 3 ) is the La in each layer 2 O 3 is the percentage by weight of m min (La 2 O 3 ) is the La of all layers 2 O 3 is a minimum percentage by weight of m (Y 2 O 3 ) is the Y in each layer 2 O 3 is the percentage by weight of m max (Y 2 O 3 ) is the Y of all layers 2 O 3 is the maximum percentage by weight of 13. A blank according to any one of claims 9 to 12, wherein f is in the range of 0.01 to 1.00, in particular in the range of 0.03 to 0.20, preferably in the range of 0.06 to 0.10, particularly preferably in the range of 0.065 to 0.085, and most preferably in the range of 0.081 to 0.

083.

14. 14. A blank according to any one of claims 1 to 13, comprising at least two different layers formed of at least one first oxide ceramic material and one second oxide ceramic material, the layers of oxide ceramic material exhibiting a continuous change in composition from the composition of the first oxide ceramic material to the composition of the second oxide ceramic material.

15. 15. A blank according to any one of claims 1 to 14, wherein the oxide ceramic is based on stabilized tetragonal zirconia polycrystal.

16. 16. A blank according to any one of claims 1 to 15, suitable for producing a multi-unit dental restoration, preferably a dental restoration comprising two or more units, in particular a bridge comprising two or more units.

17. 17. The blank of any one of claims 1 to 16, wherein the at least two different layers have different colors.

18. A distortion coefficient of less than 0.4, in particular less than 0.35, in particular less than 0.3, preferably less than 0.25, even more preferably less than 0.2, and most preferably less than 0.

1. [0050] 18. The blank according to claim 1, wherein the coefficient is calculated based on at least one measurement of HV for each of the different layers, During the ceremony, HV is the Vickers hardness measured according to ISO 14705:2008 in the range of loads from 2.5 to 5.0 kgf (24.517 to 49.034 N), in particular at a load of 5.0 kgf (49.034 N); HV max is the maximum measured value of HV, HV min is the minimum value of the HV measurements, [006] is the arithmetic mean of the HV measurements; blank.

19. A multilayered oxide ceramic green body for producing a dental restoration, wherein the oxide ceramic is based on zirconia and the multilayered oxide ceramic green body comprises at least two different layers, at least one layer comprising at least one colouring element selected from Fe, Cr, Er, Pr, Mn and Tb, and at least one layer comprising 0.005 to 5 wt % La. 2 O 3 and at least one layer comprises 0.1 to 20.0 wt % Y 2 O 3 and the at least two different layers include those La 2 O 3 and Y 2 O 3 wherein the lowest Y 2 O 3 The layer having the La content 2 O 3 1. A multilayer oxide ceramic green body comprising:

20. At least one layer is Al 2 O 3 and / or MgO, and preferably at least one layer contains La 2 O 3 and at least one other layer is Al 2 O 3 and / or MgO.

21. 21. A blank according to any one of claims 1 to 18 or a green body according to claim 19 or 20, wherein the sintering behavior of the at least two different layers is adjusted so that the blank or green body can be sintered without distortion.

22. A process for producing a blank according to any one of claims 1 to 18 or 21 or a green body according to any one of claims 19 to 21, comprising the steps of: (a) at least a first oxide ceramic material and a second oxide ceramic material are provided, the first oxide ceramic material and the second oxide ceramic material differing with respect to their chemical composition; (b) La 2 O 3 is added to at least one of the oxide ceramic materials; and (c) optionally, Al 2 O 3 and / or MgO is added to at least one oxide ceramic material; process.

23. At least one oxide ceramic material is 2 O 3 or at least one oxide ceramic material is infiltrated with La 2 O 3 and / or at least one oxide ceramic material is coated with Al. 2 O 3 and / or MgO is infiltrated or at least one oxide ceramic material is infiltrated with Al 2 O 3 and / or MgO.

24. moreover (d) forming layers of said oxide ceramic material and placing said layers one on top of the other; (e) the oxide ceramic material is compacted, in particular compressed, in order to obtain the green body; 24. The process according to claim 22 or 23, wherein (f) optionally, the green body is pre-sintered in order to obtain the pre-sintered ceramic blank.

25. 25. The process of claim 24, wherein the layer of oxide ceramic material exhibits a continuous change in composition from the composition of the first oxide ceramic material to the composition of the second oxide ceramic material.

26. A process for producing a dental restoration, in which a blank according to any one of claims 1 to 18 and 21 or a green body according to any one of claims 19 to 21 is used.

27. 27. The process according to claim 26, wherein the blank or green body is given a desired geometric shape with the aim of obtaining a shaped ceramic product, said shaping being preferably carried out by machining, particularly preferably using CAD / CAM processes.

28. 28. The process according to claim 27, wherein the shaped ceramic product has the shape of a dental framework or abutment, or a monolithic fully anatomical dental restoration, in particular a multi-unit dental restoration.

29. 29. The process of claim 27 or 28, further comprising sintering the shaped ceramic product to denseness.

Citation Information

Patent Citations

  • Uniformly coloured ceramic framework and colouring solution

    EP1486476A1

  • Process for preparing colored blank and die part

    JP2007314536A

  • A method for manufacturing colored ceramic sintered bodies, particularly for dental applications.

    JP2010501465A

  • Block and method of making

    US20070272120A1

  • Process for the preparation of colored blanks and dental shaped parts

    US20070292597A1